Paleomagnetic studies of the Lower Devonian gray deposits of Podolia - V. G. Bakhmutov; M. Teiser-Elenskaya; M. Kadzyalko-Hofmokl; L. Konstantinenko; E. B. Polyachenko (Геофизический журнал, 2012)
New results of paleomagnetic studies of Lower Devonian sediments from the southwest of Ukraine (the Podolia area, the Dniester river basin) have been presented. The samples are grey limestone and dolomite of Tiverian series comparable with the Lochkovian stage of the Geological time scale. Stable component of magnetization of the most samples indicate to remagnetization of rocks (the Permian pole, ϕ=45qS, λ=340qE, dp/dm=2q/5q). In some samples of the Ivanev suite the primary component of magnetization (Lower Devonian direction) has been distinguished. Paleomag-netic pole (ϕ=0q, λ=329qE, dp/dm=10q/12q) is in a good agreement with Lower Devonian fragment of apparent wander path for the Baltica. The results are in agreement with earlier data of authors for Silurian gray sedimentary rocks of Podolia.